Thinking mesolithic - Kozłowski, Stefan Karol 1938-2022 (Oxbow Books, 2009)
Studies of the European Mesolithic have gone through a renaissance since the seminal Warsaw conference on the subject in 1973, and Stefan Kozlowski has been at its heart. This book presents a comprehensive, re-edited selection of his most important writings on the subject, along with new papers written especially for this edition.
Keywords: Mesolithic period / Europe; Human ecology / Europe / History; Prehistoric peoples / Europe; Industries, Prehistoric / Europe; Excavations (Archaeology) / Europe; Funde; Geschichte; Excavations (Archaeology) -- Europe; Human ecology -- Europe -- History; Industries, Prehistoric -- Europe; Mesolithic period -- Europe; Prehistoric peoples -- Europe; Ausgrabung; Mesolithikum; Europe / Antiquities; Europe / History, Local; Europa; Europe -- Antiquities; Europe -- History, Local